Nuclear early warning in South Asia: problems and issues - Ramana, M.V.; Mian, Zia; Rajaraman, R. (2004)
India's 1999 Draft Nuclear Doctrine proposed the setting up of `effective intelligence and early warning capabilities', to provide early warning, communications, damage/detonation assessment'. Pursuing this policy, India has started acquiring key components of such an early warning network, including the Green Pine radar from Israel. Pakistan too has hinted at matching Indian plans for putting in place early warning systems. Against this background this study examines the different ingredients that go into the setting up of early warning systems and assesses their effectiveness. Using the insights gained from the study it also draws policy inferences about the viability and advisability of early warning systems in south Asia. - Reproduced.
Keywords: Nuclear energy - South Asia; Nuclear energy